2017
DOI: 10.3389/fncir.2017.00015
|View full text |Cite
|
Sign up to set email alerts
|

Novel Neuromodulation Techniques to Assess Interhemispheric Communication in Neural Injury and Neurodegenerative Diseases

Abstract: Interhemispheric interaction has a major role in various neurobehavioral functions. Its disruption is a major contributor to the pathological changes in the setting of brain injury such as traumatic brain injury, peripheral nerve injury, and stroke, as well as neurodegenerative diseases. Because interhemispheric interaction has a crucial role in functional consequence in these neuropathological states, a review of noninvasive and state-of-the-art molecular based neuromodulation methods that focus on or have th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 170 publications
(205 reference statements)
0
14
0
Order By: Relevance
“…6 This is consistent with emerging evidence that rTMS modulates interhemispheric connectivity, which also is affected by TBI. 18 Further, animal models have successfully used rTMS to restore cortical excitability, 19 which is often compromised following TBI. 20 A prevailing concern limiting the study of rTMS in the setting of TBI is that these patients may be at higher risk of seizures, which is a rare side effect of rTMS 9 and a common complication of severe TBI.…”
Section: Introductionmentioning
confidence: 99%
“…6 This is consistent with emerging evidence that rTMS modulates interhemispheric connectivity, which also is affected by TBI. 18 Further, animal models have successfully used rTMS to restore cortical excitability, 19 which is often compromised following TBI. 20 A prevailing concern limiting the study of rTMS in the setting of TBI is that these patients may be at higher risk of seizures, which is a rare side effect of rTMS 9 and a common complication of severe TBI.…”
Section: Introductionmentioning
confidence: 99%
“…Despite large variability in the baseline MSE measurements, HD-tDCS over premotor cortex, as hypothesized, led to significant and more reliable changes in MSE than HD-tDCS over the motor hotspot. Given that HD-tDCS over premotor cortex led to more reliable changes in cortical excitability, it is likely this was also captured in the MSE changes found in both hemispheres (i..e., an enhancement of the excitability in the stimulated hemisphere associated with a decrease of the excitability in the contralateral hemisphere 53,54 ). In line with previous studies 33 , MSE and functional connectivity seemed to be complementary metrics: MSE may be more sensitive and able to capture local changes in the motor network whereas traditional rs-fMRI functional connectivity would capture more robust changes between distant brain areas.…”
Section: Discussionmentioning
confidence: 97%
“…Growing amounts of evidence from human and animal studies are establishing neuromodulation as an effective mechanism to strengthen and promote cortical functions 54 . The behavioral results indicate that both rTMS and EPG treatment have led to considerable improvement in sensorimotor functions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, removing the afferents of the "good hand" via tourniquet-induced anesthesia, anesthetic block, and constraint induced therapy lead to improved hand function 15,16 . Harnessing the brain's innate plasticity mechanisms through non-invasive methods such as transcranial magnetic stimulation (TMS) has recently gained interest for use in functional and behavioral research as well as rehabilitation research after brain injury [17][18][19][20][21][22] and neurodegenerative diseases [23][24][25][26][27][28] . Various studies showed promising results using TMS in humans 17,25,29 , primates 30,31 , and rodents [32][33][34][35][36] .…”
Section: Introductionmentioning
confidence: 99%